Правовий реалізм як напрям соціологічної юриспруденції - Волошенюк, О. В.; Volosheniuk, O. V.; ORCID: http://orcid.org/0000-0001-8978-0645 (Вісник Харківського національного університету імені В. Н. Каразіна. Сер.: Право. - 2020. - Вип. 29. - С. 29-35, 2020)
Розкрито особливості правового реалізму як особливого напряму соціологічної юриспруденції. Розглянуто історичні передумови формування американського правового реалізму. Наголошено на тому, що правовий реалізм виник як реакція на формальний принцип прийняття судових рішень, який наполягав на необхідності суворого слідування прецедентному праву. Наведено порівняння поглядів представників правового реалізму. З‘ясовано, що попри відсутність єдності позицій прибічників правового реалізму їх об‘єднує недооцінка позитивного права як чинника визначеності і стабільності правових відносин, інструментальний підхід до права та надмірна психологізація процесу прийняття судових рішень. Відзначено, що незважаючи на суттєві недоліки, притаманні правовому реалізму, даний напрям юридичної думки здійснив істотний вплив на загальну теорію і філософію права завдяки поєднанню методів соціологічного і психологічного дослідження правової реальності і розкриттю внутрішніх механізмів формування судової практики.

The article is devoted to the disclosure of features of legal realism as a special direction of sociological jurisprudence. The historical prerequisites for the formation of American legal realism are considered. It was emphasized that legal realism emerged as a reaction to the formal principle of adjudication, which insisted on the need for strict adherence to case law. The leader of American legal formalism, K. Langdell, viewed law as a combination of legal concepts derived by inductively generalizing previous court decisions. It has been proven that one of the first to disagree with this approach was judges of U.S. Supreme Court Justice O. Holmes and B. Cardozo. A comparative analysis of the views of K. Llewellyn and J. Frank, who are recognized leaders of the movement of legal realism, was done. It was established that K. Llewellyn considered that law is not only the judge decide but also any other persons with powers over the disputes. He paid particular attention to the study of the activities of the High Courts and emphasized the need to use the so-called Grand-style in the judicial decision-making process, which allows the law to be adapted to the real circumstances of the case and to contemporary social change. In contrast, J. Frank insisted that the judge was the creator of the law, and that the courts of first instance played a major role in the administration of justice. In his opinion, one of the decisive factors in the administration of justice is the personality of the judge, his individual and psychological qualities. It has been found that despite the lack of unity of positions of the supporters of legal realism, they are united by the underestimation of positive law as a factor of certainty and stability of legal relations, an instrumental approach to law and excessive psychologization of the judicial process. It is concluded that despite the significant shortcomings inherent in legal realism, this line of legal thought has made a significant impact on the general theory and philosophy of law through the combination of methods of sociological and psychological study of legal reality and the disclosure of internal mechanisms of formation judicial decisions.

Раскрыты особенности правового реализма как особого направления социологической юриспруденции. Рассмотрены исторические предпосылки для формирования американского правового реализма. Отмечено, что правовой реализм возник как реакция на формальный принцип принятия судебных решений, который настаивал на необходимости строгого следования прецедентному праву. Приведены сравнения взглядов представителей правового реализма. Выяснено, что, несмотря на отсутствие единства позиций сторонников правового реализма, их объединяет недооценка позитивного права как фактора определенности и стабильности правовых отношений, инструментальный подход к праву и чрезмерная психологизация процесса принятия судебных решений. Отмечено, что, несмотря на существенные недостатки, присущие правовому реализму, данное направление юридической мысли оказало существенное влияние на общую теорию и философию права благодаря сочетанию методов социологического и психологического исследования правовой реальности и раскрытию внутренних механизмов формирования судебной практики.
Legal realism as direction of sociological jurisprudence
Правовой реализм как направление социологической юриспруденции
Волошенюк, О. В. Правовой реализм как направление социологической юриспруденции / Волошенюк О. В. // Вісник Харківського національного університету імені В. Н. Каразіна. Сер.: Право. - 2020. - Вип. 29. - С. 29-35. - DOI: 10.26565/2075-1834-2020-29-03.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; праворозуміння; legal understanding; правопонимание; правовий реалізм; legal realism; правовой реализм; соціологія права; sociology of law; социология права; судова правотворчість; judicial law-making; судебное правотворчество; судовий прецедент; judicial precedent; судебный прецедент; погляди вчених; views of scientists; взгляды ученых